Analysis of the needs basic physics teaching materials in industrial engineering major - Diana Ayu Rostikawati; Asep Saefullah (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2022)
This study aims to analyze the needs of students for basic physics teaching materials  in industrial engineering major. This study is an exploratory descriptive study with the subject of industrial engineering students who have taken basic physics courses. The sample used for this study was taken randomly with a total sample of 109 students. Data of study was obtained from filling out a questionnaire on the needs of teaching materials. The results of questionnaire analysis of the needs for teaching materials indicate that students want teaching materials that can make them active in learning, teaching materials whose contents begin with context in everyday life, can facilitate students to study in groups, and can improve skills in the world of work. As a follow-up to the results of questionnaire analysis, it is immediately necessary to develop basic physics teaching materials in industrial engineering major.